Tourist’s mobilities: Walking, cycling, driving and waiting - Hannam, K. (2021)
This article examines recent research in terms of tourist’s mobilities in terms practices of walking, cycling and driving. It concludes by reflecting on the contemporary lock down of travel in terms of the global pandemic and its consequences for waiting, stillness and immobility – particularly in terms of flying.